Band gap and electronic structure of defects in the ternary nitride BP3N6: experiment and theory. Issue 16 (4th April 2022) - de Boer, Tristan; Fattah, Md. Fahim Al; Amin, Muhammad Ruhul; Ambach, Sebastian J.; Vogel, Sebastian; Schnick, Wolfgang; Moewes, Alexander
Abstract : The electronic properties, including the band gap and presence of defects, of the novel ternary nitride BP3 N6 are elucidated using synchrotron radiation. Abstract : Recent advances in methods to access nitride systems by a high-pressure high-temperature approach have made possible the one-step synthesis of mixed ternary non-metal nitrides. As a prerequisite to use in a practical device, it is important to understand important bulk electronic properties, such as the band gap, as well as characterizing the presence and effect of defects that are present. In this work, the novel ternary nitride BP3 N6 is studied using techniques sensitive to the partial electronic density of states, specifically X-ray absorption spectroscopy and X-ray emission spectroscopy. Complementary full-potential all-electron density functional theory (DFT) calculations allow important bulk electronic parameters, such as the band gap, to be elucidated. The band gap of BP3 N6 has been determined to be 3.9 ± 0.2 eV and 4.1 ± 0.4 eV at the B K- and N K-edges, respectively. This is close to a theoretical value of 4.3 eV predicted by the PBEsol exchange–correlation functional and considerably less than a value of 5.8 eV predicted by the modified Becke–Johnson exchange–correlation functional. X-Ray excited optical luminescence (XEOL) measurements are performed to interrogate the presence of point defects in this system. Together with DFT calculations, these measurements reveal the presence of nitrogen vacancies which lead to multiple mid-gap trap states.